Optimization of the Artemisia Polysaccharide Fermentation Process by Aspergillus niger - Tao, Ali; Feng, Xuehua; Sheng, Yajing; Song, Zurong (Frontiers in Nutrition, 2022)
In order to investigate the fermentation process of Artemisia polysaccharides, this paper investigated the effects of fermentation time, fermentation temperature, strain inoculum, Artemisia annua addition and shaker speed on the polysaccharide production of Artemisia annua, and determined the extraction rate of Artemisia polysaccharide content based on the optimization of single-factor test, and then conducted a response surface test with temperature, inoculum and time as response variables and the extraction rate of Artemisia polysaccharides as response values, the fermentation process was optimized and the antioxidant activity of Artemisia polysaccharides was monitored using DPPH-, ABTS+, OH- and total reducing power. ---- The optimum fermentation process was determined by the test to be 5% inoculum of Aspergillus niger, temperature 3°C, time 2d6, shaker speed 180r/min, and 4% addition of Artemisia annua, and the extraction of Artemisia polysaccharides was up to 17.04 % by this condition of fermentation. The polysaccharides from Artemisia annua fermented by Aspergillus Niger had scavenging effects on DPPH, ABTS and OH.